Wage Determination and the Bite of Collective Contracts in Italy and Spain: Evidence from the Metalworking Industry - Effrosyni Adamopoulou; Ernesto Villanueva (Institute of Labor Economics (IZA), 2020)
In several OECD countries employer federations and unions fix skill-specific wage floors for all workers in an industry. One view of those "explicit" contracts argues that the prevailing wage structure reflects the labor market conditions back at the time when those contracts were bargained, with little space for renegotiation. An alternative view stresses that only workers close to the minima are affected by wage floors and that the wage structure reacts to current labor market conditions. We disentangle both models using a novel dataset that combines more than 1,000 signature dates and 15,000 wage floors set in the metalworking industry with labor market histories of metalworkers drawn from Social Security records in Italy and Spain. An increase in the contemporaneous local unemployment rate of 1 p.p. diminished contemporaneous mean wages by about 0.45 p.p. between 2005 and 2013 in both countries. Instead, a 1 p.p. higher unemployment rate back at the time of contract renewal reduced wages by 0.07 p.p., an impact driven by wages close to the negotiated wage floors. Even though the evidence for earlier periods is mixed in Italy, the results do not support the view that the wage structure reflects labor market conditions at the time of bargaining. The response of wages to local unemployment was driven by reductions in complements and employee churning, although the elasticity falls short of the prediction of an off-the-shelf bargaining model.
Keywords: J31; J38; J52; 330; minimum wages; collective contracts; Social Security data; spot market; explicit contracts; wage cyclicality